'Real-world' observational studies in arrhythmia research: data sources, methodology, and interpretation. A position document from European Heart Rhythm Association (EHRA), endorsed by Heart Rhythm Society (HRS), Asia-Pacific HRS (APHRS), and Latin America HRS (LAHRS). Issue 5 (14th November 2019) - Torp-Pedersen, Christian; Goette, Andreas; Nielsen, Peter Bronnum; Potpara, Tatjana; Fauchier, Laurent; John Camm, Alan; Arbelo, Elena; Boriani, Giuseppe; Skjoeth, Flemming; Rumsfeld, John; Masoudi, Frederick; Guo, Yutao; et al.
Abstract: The field of observational studies or "real world studies" is in rapid development with many new techniques introduced and increased understanding of traditional methods. For this reason the current paper provides an overview of current methods with focus on new techniques. Some highlights can be emphasized: We provide an overview of sources of data for observational studies. There is an overview of sources of bias and confounding. Next There is an overview of causal inference techniques that are increasingly used. The most commonly used techniques for statistical modelling are reviewed with focus on the important distinction of risk versus prediction. The final section provides examples of common problems with reporting observational data.